Feasibility of using a transition diabetes team to commence injectable therapies postdischarge from a tertiary hospital: a pilot, randomised controlled trial - Leonid Churilov; Elif I Ekinci; Felicity Pyrlis; Rajna Ogrin; Sonja Arthur; Cathy Zhai; Jeffrey D Zajac (BMJ Open, 2019)
Objectives This study aimed to investigate if the use of a transition team was feasible for patients with diabetes being discharged from hospital on injectable diabetes therapies.Design Pilot, randomised controlled trial.Setting The trial was conducted between 2014 and 2016 conjointly by a tertiary referral hospital and a community healthcare provider.Participants Hospital inpatients (n=105) on new injectable diabetes therapies were randomised 1:1 to transition team or standard care. The transition team received in-home diabetes education 24–48 hours postdischarge, with endocrinologist review 2–4 weeks and 16 weeks postdischarge.Main outcome measures The primary outcome was feasibility, defined by percentage of patients successfully receiving the intervention. Secondary outcomes included safety, defined by hospital readmission and emergency department presentations within 16 weeks postrandomisation, and treatment satisfaction, measured using Diabetes Treatment Satisfaction Questionnaire (DTSQ). Exploratory outcomes included length of stay (LOS) and change in haemoglobin A1c (HbA1c) throughout the study.Results The intervention was deemed feasible (85% (95% CI 73% to 94%)). No difference in safety between groups was detected. No difference in change in HbA1c between groups was detected (standard care median HbA1c −1.5% (IQR −3.7% to −0.2%) vs transition team median HbA1c −1.9% (IQR −3.8% to −0.2%), p=0.83). There was a trend towards reduced LOS in the transition team group (per protocol, standard care median LOS 8 (IQR 5.5–12); transition team median LOS 6 (IQR 3–12), p=0.06). There was a significant improvement in patient satisfaction in the transition team (standard care median 10.5 (IQR 8.5–16); transition team DTSQ change version median 15 (IQR 10–17.5), p=0.047), although interpretability is limited by missing data.Conclusion This study demonstrated that the use of a novel transition diabetes team is a feasible alternative model of care.